A study on the service quality performance at the Health Unit Universiti Teknologi MARA (UiTM), Kedah / Ahmad Fahmi Abdul Rashid...[et al.] - Abdul Rashid, Ahmad Fahmi; Omar, Khairil Azwan; Mohamad Salim, Mohamad Norhazman; Mohamad Yusof, Mohamad Yuzaimi (2010)
The service quality of an organization or a company is very important as it will affect performance of the organization. If the quality of services provided is adequate and good, the organization may perform well. This is due to the efficiency and effectiveness of the organization to operate in doing its business. Reflect to that, the good quality of service may increase the satisfaction of the customers who come to deal with the organization. So, it may encourage the loyalty of customers for the organization and increase the number of the customers that may come to deal with them. The purpose of this research is to study on the factors that may lead to the service quality performance at the Health Unit in UiTM Kedah. It will covers tangibles, reliability, responsiveness, assurance and empathy value within organization. The researcher will use stratified sampling technique in order to collect necessary data for this research. The researcher will choose randomly the student to become as the respondent from the various courses in UiTM Kedah.